NEGOTIATION STRATEGIES WITHIN REVERSE LOGISTICS COOPERATION - Tomasz MAŁKUS; Andrzej KOZINA (Modern Management Review)
The objective of the paper is to present specificity of strategies, as well as styles of collaboration useful for negotiations of cooperation terms in the area of reverse logistics. The content of the article is the result of considerations conducted using desk research and analysis of bibliographic sources, primarily in the field of organization of activities in reverse logistics, conditions of cooperation with specialized service providers and negotiation strategies. Also, the experience of authors in the field of conflict management in logistics systems, both within an individual enterprise, as well as between cooperating enterprises is used in the research. The content of the article presents developed proposals of negotiation strategies in bilateral relations and in relations in which there are more participants. The main guidelines for the implementation of presented proposals of negotiation strategies are also included.